Bullous papular urticaria secondary to insect sting. - Bonifazi, E.; Greco, I. (European Journal of Pediatric Dermatology, 2006)
Case 1. A 6-year-old boy presented episodes of blisters on the lower limbs, started 3 years before and recurring in late spring and summer. Hospitalized many times, he carried out various examinations ruling out autimmune blistering disorders. On physical examination, there were 3 tense blisters, about 2 cm in diameter on the left leg and 2 hypomelanic residua with clear-cut borders on the right leg. The final diagnosis was bullous papular urticaria. Case 2. 5-year-old boy with blistering episodes only in late spring. On the right leg there were a 2 cm in size blister, an erosion and 2 hypomelanic residua, on the left leg there was a 2 cm in size erythematous patch centered by a 2 mm in size vesicle. History: initially itchy erythema; on it then appears a central vesicle, which rapidly enlarges, till turning into a blister covering the entire erythematous area. Final diagnosis: bullous papular urticaria.